Jejunal diverticulitis. Issue 1 (31st January 2019) - Prough, Haley; Jaffe, Sarah; Jones, Brian
Abstract: Cases of small bowel diverticulitis, excluding Meckel's diverticulitis, are rare. Small bowel diverticular disease has been reported in approximately 0.3–1.3% cases of post mortem studies (Fisher JK, Fortin D. Partial small bowel obstruction secondary to ileal diverticulitis. Radiology 1977;122:321–322.) and in only 0.5–1.9% of contrast media study cases (Cattell RB, Mudge TJ. The surgical significance of duodenal diverticula. N Engl J Med 1952;246:317–324). Diverticula located within the small bowel may have presentations and complications similar to that of colonic diverticular disease. However, there is no consensus for the management for small bowel diverticulitis. Given that small bowel diverticulitis, like a colonic diverticulitis, can cause an acute abdomen, surgical intervention may be required. In this particular case, a patient presented with symptoms of lower abdominal pain, nausea and fever. Following an x-ray and CT scan, the patient underwent an open laparotomy and small bowel resection of a portion of jejunum that contained a symptomatic diverticulum.